Telangiectatic Mastocytosis: If It Is Not Mastocytosis, What Is It? Comment on Brockow et al. Challenges in the Diagnosis of Cutaneous Mastocytosis. Diagnostics 2024, 14, 161 - Francisco Urbina; Alicia Benavides (Diagnostics)
We read with great interest the recent review of Brockow et al [...]